Sea ice presence is linked to higher carbon export and vertical microbial connectivity in the Eurasian Arctic Ocean - Fadeev, Eduard; Rogge, Andreas; Ramondenc, Simon; Nöthig, Eva-Maria; Wekerle, Claudia; Bienhold, Christina; Salter, Ian; Waite, Anya M.; Hehemann, Laura; Boetius, Antje; Iversen, Morten H. (Communications biology, 2021)
Arctic Ocean sea ice cover is shrinking due to warming. Long-term sediment trap data shows higher export efficiency of particulate organic carbon in regions with seasonal sea ice compared to regions without sea ice. To investigate this sea-ice enhanced export, we compared how different early summer phytoplankton communities in seasonally ice-free and ice-covered regions of the Fram Strait affect carbon export and vertical dispersal of microbes. In situ collected aggregates revealed two-fold higher carbon export of diatom-rich aggregates in ice-covered regions, compared to Phaeocystis aggregates in the ice-free region. Using microbial source tracking, we found that ice-covered regions were also associated with more surface-born microbial clades exported to the deep sea. Taken together, our results showed that ice-covered regions are responsible for high export efficiency and provide strong vertical microbial connectivity. Therefore, continuous sea-ice loss may decrease the vertical export efficiency, and thus the pelagic-benthic coupling, with potential repercussions for Arctic deep-sea ecosystems. Fadeev et al. explore carbon export dynamics along the water column using microscopic analysis, 16S rRNA gene amplicon sequencing, and physical modeling of data from long-term sediment traps in the Fram Strait. Their results indicate that larger aggregates from sea-ice and under-ice diatom blooms are responsible for higher export efficiency and vertical microbial connectivity, suggesting that continuous sea-ice loss may result in decreased pelagic-benthic coupling, with resultant impacts on marine food webs.